(untitled) (Sustainability in Debate, 2016)
This study seeks to describe and analyze the socioproductive inclusion strategies adopted by members of the Associação de Mulheres ’Resgatando Sua História’, a women’s organization located in the Lagoa da Volta community, municipality of Porto da Folha, in the interior of the state of Sergipe. At the same time it discusses agroecology as a strategy for coexistence with the semiarid climate. Methodologically, a case study of the association was conducted in 2015, based on 12 semi-structured interviews, photographic and audio records, and field notes. It is noteworthy that the women in the association engage in several agricultural and non-agricultural activities that directly contribute to their income, to household food security and to coexistence with the semiarid climate. Interviewees organize their socioproductive strategies through associativism, which together with the agroecological activities are a form of socioproductive and participatory inclusion of women and of sustainable coexistence with the semiarid climate, improving their living conditions.